Improving the efficacy and reliability of rTMS language mapping by increasing the stimulation frequency - Nettekoven, Charlotte; Pieczewski, Julia; Neuschmelting, Volker; Jonas, Kristina; Goldbrunner, Roland; Grefkes, Christian; Weiss Lucas, Carolin (Human brain mapping)
Repetitive TMS (rTMS) with a frequency of 5-10~Hz is widely used for language mapping. However, it may be accompanied by discomfort and is limited in the number and reliability of evoked language errors. We, here, systematically tested the influence of different stimulation frequencies (i.e., 10, 30, and 50 Hz) on tolerability, number, reliability, and cortical distribution of language errors aiming at improved language mapping. 15 right-handed, healthy subjects (m~=~8, median age: 29 yrs) were investigated in two sessions, separated by 2-5 days. In each session, 10, 30, and 50 Hz rTMS were applied over the left hemisphere in a randomized order during a picture naming task. Overall, 30 Hz rTMS evoked significantly more errors (20 $±$ 12{%}) compared to 50 Hz (12 $±$ 8{%}; p {<}.01), whereas error rates were comparable between 30/50 and 10~Hz (18 $±$ 11{%}). Across all conditions, a significantly higher error rate was found in Session 1 (19 $±$ 13{%}) compared to Session 2 (13 $±$ 7{%}, p {<}.05). The error rate was poorly reliable between sessions for 10 (intraclass correlation coefficient, ICC~=~.315) and 30 Hz (ICC~=~.427), whereas 50 Hz showed a moderate reliability (ICC~=~.597). Spatial reliability of language errors was low to moderate with a tendency toward increased reliability for higher frequencies, for example, within frontal regions. Compared to 10~Hz, both, 30 and 50 Hz were rated as less painful. Taken together, our data favor the use of rTMS-protocols employing higher frequencies for evoking language errors reliably and with reduced discomfort, depending on the region of interest.
Keywords: Adult; Brain Mapping; Cerebral Cortex/diagnostic imaging/physiology; Female; Humans; Magnetic Resonance Imaging; Male; Pattern Recognition; Psycholinguistics; Reproducibility of Results; Speech/physiology; Transcranial Magnetic Stimulation; Visual/physiology; Young Adult